(untitled) (Fiep Bulletin - online, 2016)
The motor praxeology is an epistemological, scientific, methodological and pedagogical body that tries to understand the world of games, sports and other motor practices from the study of the internal logic of these activities. The praxeologic knowledge makes use of instruments and methods to understand the internal logic (properties) of physical activities without, however, compromising the sense of the external logic. Through this process, the motor behavior pedagogy takes a relevant role in the curricular, didactic and methodologic design in the educational context. As a theoretic and scientific framework, it defines and puts in context themes like the game as a sociological praxeologic system. Parlebas, (2001), Lagardera e Lavega, (2003); Huizinga (2003). Epistemological, pedagogical, theoretical and methodological principles of motor praxeology, “the Science that studies motor action” Parlebas (2001), is a relevant knowledge area to human motricity. It allows us to understand the grammar of the motor practices from the motor actions. Therefore, the authors teach us to investigate the motor behavior by considering that each game or sport demands an internal logic, and that every motor practice constitutes a praxiologic system.